2018
DOI: 10.1128/jb.00540-17
|View full text |Cite
|
Sign up to set email alerts
|

Pseudouridine-Free Escherichia coli Ribosomes

Abstract: Pseudouridine (Ψ) is present at conserved, functionally important regions in the ribosomal RNAs (rRNAs) from all three domains of life. Little, however, is known about the functions of Ψ modifications in bacterial ribosomes. An strain has been constructed in which all seven rRNA Ψ synthases have been inactivated and whose ribosomes are devoid of all Ψs. Surprisingly, this strain displays only minor defects in ribosome biogenesis and function, and cell growth is only modestly affected. This is in contrast to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…This enzyme modifies uridine into pseudouridine at certain positions of the 23S rRNA and tRNAs (Raychaudhuri et al, 1999). It was suggested that these modifications play a role in the stability of RNA and ribosome biogenesis (Cabello-Villegas and Nikonowicz, 2005;O'Connor et al, 2017). Furthermore, RNase E participates in rRNA and tRNA maturing processes (Mackie, 2013), and therefore it could increase the levels of these RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme modifies uridine into pseudouridine at certain positions of the 23S rRNA and tRNAs (Raychaudhuri et al, 1999). It was suggested that these modifications play a role in the stability of RNA and ribosome biogenesis (Cabello-Villegas and Nikonowicz, 2005;O'Connor et al, 2017). Furthermore, RNase E participates in rRNA and tRNA maturing processes (Mackie, 2013), and therefore it could increase the levels of these RNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical modifications of RNA occur in organisms from all kingdoms of life and are often highly conserved throughout evolution, as is the case of the methylation of carbon-5 in cytosines (Huber et al, 2015;Boccaletto et al, 2017). Despite that, there is a growing body of evidence showing that several RNA modifications are individually not required for development under controlled conditions (O'Connor et al, 2018, reviewed in Sharma & Lafontaine, 2015and Hopper & Phizicky, 2003. Our results reignite a recurrent question in the epitranscriptomics field: why are so many of these chemical marks extensively conserved throughout evolution and, yet, organisms often present subtle phenotypes in their absence?…”
Section: Discussionmentioning
confidence: 99%
“…These include single nucleotide substitutions and deletion of a nucleotide in the tip of H69 43 . Furthermore, removal of three pseudo-uridylation sites (PSU 1911, 1915, and 1917) by deletion of the responsible pseudo-U synthase RluD causes little to no phenotype in E. coli 44 . While complete deletion of H69 does not affect translation significantly, ΔH69 50S subunits show subunit association defects, emphasizing the role of this bridge for stabilizing 70S ribosomes 45 .…”
Section: Discussionmentioning
confidence: 99%